( x - 2 ) ( x + 1 ) = ( x - 1 ) ( x + 3 )
Answers
Answered by
1
So solove it so
x-2+x+1 = x-1+x+3
2x-1 = 2x+2
Change their places so their signs will change now
2x-2x = 1+2
0x = 3
Now x = 3/0 so anwer is 0
Hope it helps u
Answered by
9
Answer :-
x = -1/3
Step-by-step explanation :-
Whenever no sign is given in between the 2 terms, or if the terms are written in brackets it means that the 2 terms are to be multiplied.
Here, let's solve the Left-hand Side (LHS) and Right Hand Side separately and later equate them.
✮ Solution:
For solving this question, we apply the algebraic identity:
- (x + a) (x + b) = x² + x (a + b) + ab
Solving LHS,
(x - 2) (x + 1)
= x² + x (-2 + 1) + -2(1)
= x² - x - 2
Solving RHS,
(x - 1) (x + 3)
= x² + x (-1 + 3) + -1(3)
= x² + 2x - 3
In the given question,
✯ LHS = RHS
⇒ x² - x - 2 = x² + 2x - 3
⇒ - x - 2 = 2x - 3
⇒ - 2 + 3 = 3x
⇒ 3x = -1
⇒ x = -1/3
Similar questions
English,
1 month ago
Social Sciences,
1 month ago
Social Sciences,
1 month ago
English,
3 months ago
Hindi,
3 months ago
Hindi,
11 months ago
Math,
11 months ago